Pengelolaan Ruang Kelas Pendidikan Anak Usia Dini Pada Kelompok B Di Taman Kanak-Kanak - Nasution, Zahra Ayuni; Nunzaurina, Nunzaurina; Shadilla, Shadilla (Jurnal Sains dan Teknologi, 2023)
The purpose of this journal is to learn about the management of class management at Pelangi Field School. As far as the writer is concerned, he took the examination at the Rainbow School because the school has already entered the advanced category and developed with proven accreditation B and numerous prizes and awards charts organized in the headquarters room and also the business room. Based on the results of the research that the management of the class at Pelangi School has been good because of the implementation of the indicators of class management which the author has published in this journal.